Sistem Informasi Tambah Daya Listrik pada PT. PLN (Persero) Rayon Kota Sabang - Saifurrahman; Alfina (Jurnal Manajemen Sistem Informasi (JMASIF), 2022)
The purpose of this research is to design and build an Information System for Adding Electrical Power at PT. PLN (Persero) District of Sabang City. Information system for adding electric power at PT. PLN (Persero) Rayon of Sabang City was built using Microsoft Visual Foxpro 9.0. At the application development stage using the Scrum software development method. The results of the study found that; 1) Prospective customers who want to know about new installation information, provide the required amount of power to the service department and information provided to prospective customers in the form of new installation information., 2) Based on the database and form creation process using Microsoft Visual Foxpro 9.0, 3) Based on database creation, the name of the database is db_adddaya, and uses 3 tables namely customer, cost, installation, and 4) Based on the form using 9 forms, namely Customer Data Input Form, Cost Data Input Form, Installation Data Input Form, Customer Assistance Form, Assistance Form Receipt, Installation Assistance Form, Installation Search Form, Report Form, Login Form.